The role of apatinib combined with paclitaxel (aluminum binding type) in platinum-resistant ovarian cancer - Hong Zhao; Rong Li; Xiaoyan Wang; Xin Lu; Min Hu; Jinbin Zhang; Xia Zhao; Xiaoqin Song; Yangyang Liu (BMC, 2020)
Abstract Objective To assess the anti-tumor activity and side effects of different dosages of paclitaxel (albumin binding type) (hereinafter referred to as nab-P) combined with Apatinib (hereinafter referred to as AP) in platinum-resistant ovarian cancer cell line and xenograft models. Methods SKOV-3/DDP cell line was selected as the research object in cytology experiment. Firstly, we divided it into three groups for experiments to explore the individual effects of nab-P and AP. a): Control group, blank control, no drug intervention; b): nab-P group, nab-P 40 μmol/l; c): AP group, AP 50 μmol/l (Drug doses were IC-50 values that detected by MTT assay). Apoptosis related protein (Bax, bcl-2), vascular related protein(p-VEGFR-2), invasion related protein (MMP-2) expression were detected by Western blot and Cellular immunofluorescence, the invasion ability of tumor cells were detected by Transwell and Cell scratch test. Based on these dates, secondly, establishing different doses of nab-P combined with Ap to explore the curative effect of combination therapy. a): Control group, blank control, no drug intervention; b): Group-1, nab-P 5 μmol/l + AP 10 μmol/l, c): Group-2, nab-P 4.5 μmol/l + AP 10 μmol/l, d): Group-3, nab-P 4 μmol/l + AP 10 μmol/l, e): nab-P group, nab-P 5 μmol/l, f): AP group, AP 10 μmol/l (MTT assay). The combination index was analyzed by Compusyn software, Western blot, Immunofluescence, Transwell and Cell scratch test also were also chose to observe of inhibition effect. Thirdly, we used xenograft models to verify the results of cytological experiments. Tumor-forming BALB/c female nude mice were randomly divided into 4 groups, a): Control group, no drug intervention, only saline injection, b): nab-P 20 mg/kg + AP 150 mg/kg, c): nab-P 18 mg/kg + AP 150 mg/kg, d): nab-P 16 mg/kg + AP 150 mg/kg (The doses were guided by the pharmaceutical manufacturers). The tumor growth curve was analyzed during the experiment. And the apoptosis related protein (Bax, bcl-2), angiogenesis related protein (CD31, p-VEGFR-2) and invasion related protein (MMP-2) were observed by Western blot, Immunofluescence and Immunohistochemistry to analysis the ant-tumor effects. The quality of life in nude mice were observed to analysed the drug-induced side effects. Result In the separate medication section, (1) The IC-50 value of nab-P was 45.53 ± 4.06 μmol/l, while the AP was 50.66 ± 4.96 umol/L (48 h). (2) The expressions of bcl-2 (nab-P group, AP group), p-VEGFR-2 (AP group), MMP-2(nab-P group, AP group) were higher than Control group, while Bax (nab-P group, AP group) lower (P < 0.01). (3) The cell invasive ability was decreased after the nab-P and AP intervation (P < 0.01). In the combination medication section, (1) Compusyn showed the Combination index (Cl) were all below 1 (Cl < 1), that means nab-P and AP are synergism. (2) The combination IC-50 value was nab-P 5.28 μmol/l + AP 10.56 μmol/l (48 h). (3) In the detection of related protein expression, the combination of drugs can improve the anti-tumor effect, otherwise, after combined with AP, when nab-P were reduced dose in proper quantity, there were no obvious different in drug effect. (4) After reducing the doses of nab-P, the average food intake of nude mice increased from 4.50 g ± 0.17 to 5.55 g ± 0.13, and the one-hour activity increased from 6.11 min ±0.16 to 6.34 min ±0.13. Conclusion nab-P, a chemotherapeutic agent, can play an anti-tumor role in platinum-resistant ovarian cancer, but it can cause adverse effects that increase with dose. When combined with AP, the two drugs have synergistic effect, which can improve the anti-tumor effects of single drug. In addition, when combined with AP, the doses of nab-P can be appropriately reduced under the standard of recommended to reduce the toxicity of chemotherapy drugs, without affecting the anti-tumor effect.